2014
DOI: 10.5194/bg-11-4953-2014
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of ferrihydrite with adsorbed and coprecipitated organic matter: microbial reduction by <i>Geobacter bremensis</i> vs. abiotic reduction by Na-dithionite

Abstract: Abstract. Ferrihydrite is a widespread poorly crystalline Fe oxide which becomes easily coated by natural organic matter in the environment. This mineral-bound organic matter entirely changes the mineral surface properties and therefore the reactivity of the original mineral. Here, we investigated 2-line ferrihydrite, ferrihydrite with adsorbed organic matter, and ferrihydrite coprecipitated with organic matter for microbial and abiotic reduction of Fe(III). Ferrihydrite-organic matter associations with differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 68 publications
(81 reference statements)
4
67
0
1
Order By: Relevance
“…This minerotrophic, slightly acidic (pH ∼ 5) fen has been previously described in detail (Blodau et al, 2004;Eusterhues et al, 2014;Hausmann et al, 2016;Küsel et al, 2008;Loy et al, 2004;Pester et al, 2012). Briefly, granite bedrock is covered by a Fibric Histosol, often referred to as peat, with a thickness between 40 and 70 cm.…”
Section: Study Site and Sampling Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…This minerotrophic, slightly acidic (pH ∼ 5) fen has been previously described in detail (Blodau et al, 2004;Eusterhues et al, 2014;Hausmann et al, 2016;Küsel et al, 2008;Loy et al, 2004;Pester et al, 2012). Briefly, granite bedrock is covered by a Fibric Histosol, often referred to as peat, with a thickness between 40 and 70 cm.…”
Section: Study Site and Sampling Proceduresmentioning
confidence: 99%
“…Not surprisingly, microbial reduction of Fe(III) oxides like nanometer-sized lepidocrocite and ferrihydrite by Shewanella species can be boosted by the presence of humic acids (Adhikari et al, 2017;Amstaetter et al, 2012;Pé-drot et al, 2011;Shimizu et al, 2013) and quinone moieties (Newman and Kolter, 2000) when the amount of dissolved organic carbon is greater than a threshold concentration of 5-10 mg C L −1 (Jiang and Kappler, 2008). Conversely, a study by Eusterhues et al (2014) reported that high C / Fe ratios in coprecipitated and adsorbed ferrihydrite complexes inhibited the reduction of ferrihydrite by G. bremensis. Poggenburg et al (2016) produced ferrihydrite OM complexes with different organic materials (extracted extracellular polymeric substances, water extracts of soil litter) and used S. putrefaciens and G. metallireducens to reduce them.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations